Development of standardized green coffee bean extract (Coffea canephora) into effervescent granules as an antioxidant supplement - Wijaya, Andre; Darsono, Farida Lanawati; Foe, Kuncoro (Universitas Ahmad Dahlan, 2024)
This study aimed to obtain the optimum formula of effervescent granules of green coffee extract (EG-GCE) on its physical quality (flow speed, water content, and dissolving granule time test) and effectiveness as an antioxidant. The dried extract was obtained by percolation of green coffee with water and dried using a spray drier. The dry extract will be standardized for specific and non-specific. The dose of the dried extract of green coffee used in the granule effervescent was 250 mg pr sachet. EG-GCE was formulated using wet granulation method. Effervescent granules were tested for physical quality (organoleptic, pH, moisture content, flow properties, and dissolving effervescent granule time test) and effectiveness, consisting of antioxidant activity (IC50) with the DPPH method using the microplate reader. The optimum effervescent granule formula was obtained using the factorial design method. The factors used were citric acid monohydrate with a level of (-1) 8% and a level of (+1) 12%, and tartaric acid with a level of (-1) 16%and a level of (+1) 24%. The determination of the optimum formula (proportion of citric acid monohydrate and tartaric acid) was carried out by factorial design method using the following responses: moisture content, flow rate, and dissolving effervescent granule time test. Furthermore, the One Way Anova (Yate's Treatment) statistical method will analyze data from parametric experiments between batches and between formulas. If there is a significant difference in the statistical analysis between the formulas, then the test is continued using the Tukey post-hoc test method. The pH value of resulting EG-GCE products was within the range of 5.46-6.07, moisture content: 3.12-3.67%, flow rate: 25.78-28.53 g/s, angle of repose: 25.65-30.130, Hausner ratio: 1.14-1.22, Carr's index: 12.50–17.83%, dissolving effervescent granule time test: 1.00-1.33 min. This study demonstrated that citric acid monohydrate, tartaric acid, and their interaction affected the moisture content, flow rate, and effervescent time of EG-GCE. The proportion of citric acid monohydrate (9.94%) and tartaric acid (17.46%) was found to be the optimum formula of EG-GCE, with the following responses: moisture content 3.26%, flow rate 25.72 g/s, and dissolving effervescent granule time test 1.19 min. The optimum formula show strong antioxidant activity with IC50 free of radical scavenging 56.56 ± 0.97 µg/ml.